CAPITALIST STATE IN RADIOHEAD’S OK COMPUTER ALBUM: A MARXIST ANALYSIS - Farhan, Fernanda Ahmad; Ihsan, Pramudana; Yunianti, Sofi (Universitas PGRI Sumatera Barat, 2023)
This research presented an album by alternative rock band Radiohead's